Bilingualism and bilingual education in jaffna - Karunakaran, T.; Kannathas, d S.K. (University of Jaffna, 2012)
Bilingualism refers to the ability to speak two languages fluently. Multilingualism is then the mastery of more than two languages on a high level of proficiency. International surveys indicate that there are many more bilinguals and multilinguals in the world's population than there are monolinguals. In many parts of the world, children are educated through the medium of a second or foreign language. Moreover, for many people, bilingualism or multilingualism constitutes the normal every day experience. English, specifically, is crucial in today's world. English has become the world’s second language. It is claimed that the world today suffers from English fever that English is necessary if one wants to communicate with the rest of world, in business or during holidays, and this causes the increasing demand for learning English. This research was undertaken to study the current practice of bilingual education implemented in Government schools in Jaffna. This study examined current situation of bilingual education in two National schools in Jaffna. The study of bilingual education progress included interviews with students, parents and teachers, observation of classrooms and questionnaires for teachers and students. Socio-cultural factors prone to influence bilingual learning progress in Jaffna were their social status, economic status, parent’s attitude, and language preference of language use, cultural aspects of Tamil society and perceptions of bilingual education from different communities. We have described a bilingual research which took place in the national schools, Jaffna Hindu College and Vembadi Girls’ High School. Subjects of this research were students, teachers and parents. Factors of influence taken into consideration were social status, economic status, parent’s attitude, language preference of language use, cultural aspects of Tamil society perceptions of bilingual education from different communities. Responses from teacher, parents and children describe the current scenario of bilingual practice in these two schools
Keywords: Bilingualism; Bilingual education; Multilingualism